A bibliometric analysis of the research on ‘Depleted Uranium Munitions’: from health and environment to international security - Eslami, Mohammad; Fernandes, Sandra (Frontiers in Political Science, 2025)
The study of depleted uranium (DU) munitions is crucial due to their potential health risks, long-term environmental impacts, and broader implications for international security. This multidisciplinary concern spanning from health and environmental sciences to international security has prompted growing scholarly attention, yet no comprehensive bibliometric analysis has been conducted to systematically map the evolution of this field. This study fills that gap by providing a structured, data-driven overview of DU research trends over the last four decades (1983–2024). Using bibliometric tools such as Biblioshiny and VOSviewer, we analyze 129 publications from Scopus to uncover key developments in this domain. Specifically, we examine the annual distribution of publications, document types, leading journals, country collaboration networks, and the most prolific authors. Additionally, we conduct a keyword co-occurrence analysis to identify dominant research themes, track their evolution over time, and assess conceptual density within the field. Our findings highlight the historical trajectory and current state of DU munitions research, and demonstrate the lack of research in the fields of Political Science, International Relations and in a broader term International Security. The main objective of this research is to analyze the scientific findings about DU weapons, enhance awareness about them and their hazards, and provide a framework for scholars and policymakers seeking to engage with DU-related research more effectively and pave the way for the prohibition of such toxic munitions.